821 An Audit of the Use of PICC Lines in Preterm Infants (< 33Weeks) in a Tertiary Neonatal Intensive Care Unit. (October 2012) - Nosherwan, A; Gill, I; Walsh, H; Knowles, S; Twomey, A
Abstract : Aim: To study the frequency of use, indications for placement and complications associated with PICC line placement in a single tertiary NICU. Method: A prospective review of all the PICC lines inserted over ten-month period. Data was obtained from clinical notes, radiology reports and laboratory results. Results: A total of 71 lines were placed in 53 infants < 33 weeks. 43% (53/131) infants < 33 weeks admitted had PICC line placed. The mean gestational age was 27.7±2.3 weeks and mean birth weight was 1030±332g. The indications for insertion was administration of Parenteral nutrition (86%), Inotropes (11%), and antibiotics (3%). The mean age at insertion was 7±6 days and the average duration of placement was 6±5 days. All the lines were inserted with maximum sterile barrier and 86% were accessed once per day under strict sterile protocol. 35% lines were correctly placed, 64% required manipulation and post manipulation catheter tip was confirmed in 64% cases. 58% of the lines completed treatment. Line occlusion was the most common complication (17%), which significantly reduced the duration of line placement by 3.3 days (p=0.02). The infection rate was 13 per 1000 catheter days. Conclusion: There is a high rate of PICC associated complications with occlusion of lines accounting for most of these. Our NICU is reviewing whether thrombolytic agents should be considered routinely for line occlusion. Attention has been directed to ensure that line position is reconfirmed by X-ray after manipulation. Our infection rate still remains high when compared to rates quoted internationally.